2000
DOI: 10.1523/jneurosci.20-15-05748.2000
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Stress Reversibly Activates theDrosophilaLight-Sensitive Channels TRP and TRPLIn Vivo

Abstract: Drosophila transient receptor potential (TRP) is a prototypical member of a novel family of channel proteins underlying phosphoinositide-mediated Ca(2+) entry. Although the initial stages of this signaling cascade are well known, downstream events leading to the opening of the TRP channels are still obscure. In the present study we applied patch-clamp whole-cell recordings and measurements of Ca(2+) concentration by ion-selective microelectrodes in eyes of normal and mutant Drosophila to isolate the TRP and TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 64 publications
3
60
1
Order By: Relevance
“…In light of these findings we repeated some key experiments, which assumed that norpA P24 was functionally null. In particular we found that contrary to a recent report (8), activation of the light-sensitive channels by metabolic inhibitors is strictly dependent on PLC activity, and we present evidence here that this represents the failure of DGK. By contrast, excitation of the channels by PUFAs (6), suggested previously to be caused indirectly by metabolic inhibition (8) or by the activation of endogenous PLC (20), appeared to be independent of PLC activity and seems likely to represent a direct effect on the channels or their lipid environment.…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…In light of these findings we repeated some key experiments, which assumed that norpA P24 was functionally null. In particular we found that contrary to a recent report (8), activation of the light-sensitive channels by metabolic inhibitors is strictly dependent on PLC activity, and we present evidence here that this represents the failure of DGK. By contrast, excitation of the channels by PUFAs (6), suggested previously to be caused indirectly by metabolic inhibition (8) or by the activation of endogenous PLC (20), appeared to be independent of PLC activity and seems likely to represent a direct effect on the channels or their lipid environment.…”
contrasting
confidence: 99%
“…In view of the importance of these arguments for the mechanism of excitation and because of the significant PLC activity remaining in norpA P24 , we repeated and extended these experiments. We first confirmed that mitochondrial inhibitors could activate light-sensitive channels as reported previously (8). Indeed, large currents were reversibly induced within only seconds of application of either 10 M CCCP or 0.1 mM DNP in WT and norpA P24 in recordings made soon after establishing the wholecell configuration (Fig.…”
Section: Fig 3 Massive Facilitation Of Light Response In Norpa P24supporting
confidence: 87%
See 3 more Smart Citations